2014
DOI: 10.1109/taslp.2014.2327297
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis Model With Intuitive Control Capabilities for Rolling Sounds

Abstract: This paper presents a physically inspired source-filter model for rolling sound synthesis. The model, which is suitable for real-time implementation, is based on qualitative and quantitative observations obtained from a physics-based model described in the literature. In the first part of the paper, the physicsbased model is presented, followed by a perceptual experiment, whose aim is to identify the perceptually relevant information characterizing the rolling interaction. On the basis of this experiment, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…They also open up the door to new types of sound design techniques based on physical modeling of environmental sound sources that can be used for new types of tasks (e.g. [57,102,103]). Particularly, the sounds as materials metaphor may be useful here in guiding and understanding this design process, allowing greater refinement and development of sounds that can be implemented, by appreciating how design interacts relationally with the skills of a user [2,47].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also open up the door to new types of sound design techniques based on physical modeling of environmental sound sources that can be used for new types of tasks (e.g. [57,102,103]). Particularly, the sounds as materials metaphor may be useful here in guiding and understanding this design process, allowing greater refinement and development of sounds that can be implemented, by appreciating how design interacts relationally with the skills of a user [2,47].…”
Section: Applicationsmentioning
confidence: 99%
“…Research has found that listeners can perceive the speed and size of a rolling ball (to some degree of accuracy, at least) [54]. Along the lines of an ecological acoustics account, this can be explained through (and modeled by emulating) the sound-producing physics of the ball as it travels across a surface [55][56][57], providing structured information of the event. Recent research extends these findings, showing that the sound of a rolling ball can also offer sufficient affordances for action.…”
mentioning
confidence: 99%
“…This allowed the authors to categorise specific positive and negative traits in their devised system. Other works in the field have utilised qualitative processes to identify salient features in audio distractors [46] or to validate the design of sound synthesis techniques [47].…”
Section: Results: Qualitative Measuresmentioning
confidence: 99%
“…Like the control space described in section 4.2.1 that allows the user to control the perceived material and to morph continuously from one material to another (e.g., from glass to metal through a continuum of ambiguous materials), a control space that enables continuous control of evoked interactions was developed in this study (e.g., being able to synthesize a rubbing sound and slowly transform it into a rolling one). For this purpose, Conan et al (2014a) first identified invariants related to the auditory perception of interactions. Phenomenological considerations, physical modeling, and qualitative signal analysis were investigated.…”
Section: Perception Of Various Actionsmentioning
confidence: 99%